A DRD2/ANNK1–COMT Interaction, Consisting of Functional Variants, Confers Risk of Post-traumatic Stress Disorder in Traumatized Chinese - Zhang, Kunlin; Wang, Li; Cao, Chengqi; Li, Gen; Fang, Ruojiao; Liu, Ping; Luo, Shu; Zhang, Xiangyang; Liberzon, Israel (Frontiers in Psychiatry, 2018)
Objective: Post-traumatic stress disorder (PTSD) is a trauma- and stress-related psychiatric syndrome that occurs after exposure to extraordinary stressors. The neurotransmitter dopamine (DA) plays important roles in neurobiological processes like reward and stress, and a link between PTSD and the dopaminergic system has been reported. Thus, the investigation of an association between PTSD and gene–gene interaction (epistasis) within dopaminergic genes could uncover the genetic basis of dopamine-related PTSD symptomatology and contribute to precision medicine. Methods: We genotyped seven single nucleotide polymorphisms (SNPs) of three dopaminergic genes DRD2/ANNK1 (rs1800497 and rs1801028), COMT (rs6269, rs4633, rs4818 and rs4680) and DBH (rs1611115), in a Chinese predominantly adult cohort that had been exposed to an earthquake (156 PTSD cases and 978 controls). Results: Statistical genetics analysis identified a DRD2/ANNK1–COMT interaction (rs1800497×rs6269), which is associated with PTSD diagnosis (Pinteraction = 0.0008055 and Pcorrected = 0.0169155). Single-variant and haplotype-based subset analyses showed that rs1800497 modulates the association directions of both the rs6269 G allele and the rs6269-rs4633-rs4818-rs4680 haplotype G-C-G-G. The interaction (rs1800497×rs6269) was replicated in a Chinese young female cohort (32 cases and 581 controls, Pinteraction = 0.01329). Conclusions: Rs1800497 is related to the DA receptor D2 density and rs6269-rs4633-rs4818-rs4680 haplotypes affect the catechol O-methyltransferase level and enzyme activity. Thus, the interaction was inferred to be at protein–protein and DA activity level. The genotype combinations of the two SNPs indicate a potential origin of DA homeostasis abnormalities in PTSD development.